Quality Assurance Challenges in Indonesian Islamic Higher Education - Dewi Wulandari; Ivan Luthfi Amirudin; Annisa Shofiya Kamila; Muhammad Rozif Mu'ayyad Abu Fathir (Edudeena : Journal of Islamic Religious Education, 2025)
This study examines quality assurance challenges in Indonesian Islamic higher education by focusing on a case study of State Islamic Religious Colleges (PTKIN) at UIN Syekh Wasil Kediri. The analysis is conducted through five key dimensions of educational quality: students, lecturers, curriculum, facilities, and educational governance. Using a qualitative descriptive approach, data was collected through interviews, observations, and document analysis to capture institutional practices and stakeholder perspectives. The findings reveal that the main challenges in quality assurance lie in the suboptimal integration of students’ academic and spiritual development, limited mastery of learning technologies among some lecturers, a curriculum that remains predominantly theoretical, underutilization of campus facilities, and governance practices that have not fully embraced transparency and participatory principles. These issues indicate that quality assurance in PTKIN cannot be addressed through fragmented or sectoral improvements. This study confirms that strengthening educational quality requires a comprehensive and integrated quality assurance approach that aligns academic excellence, spiritual formation, and institutional management. The contribution of this research lies in offering a holistic analytical framework that illustrates the interrelated nature of quality components within PTKIN, extending existing discussions that often focus on isolated aspects of educational quality. The findings are expected to serve as a strategic reference for PTKIN policymakers and institutional leaders in developing sustainable and integrated quality assurance systems in Indonesian Islamic higher education.